Smart city security solution - Islam, Shihabul; Halim, S M Shafiul; Ador, Sadman Sakib (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.